Sex differences in the acute effect of stair-climbing on postprandial blood glucose levels: A randomized controlled trial - Jeff M. Moore; Cameron Vinoskey; Hannah Salmons; Shirin Hooshmand; Jochen Kressler (Metabolism Open, 2022)
Backgrounds and aims: Single, short stair climbing and descending (SCD) bouts of low to moderate intensity effectively lower postprandial blood glucose but previous reports have found conflicting results on interactions by sex during exercise. We hypothesize that SCD at a self-selected intensity will be equally effective at lowering postprandial blood glucose in males and females. Methods and Results: Thirty subjects (age: 23.8 (3.0) years) performed 0, 1, 3, and 10 min of SCD following consumption of a mixed meal. SCD was performed at a self-selected comfortable pace and all bouts ended at minute 28. Postprandial blood glucose was measured every 15 min for 1 h and analyzed as glucose over time, area under the curve (AUC), and incremental AUC (iAUC) using mixed-design ANOVAs with repeated measures. Although there was no interaction between sex and condition or time (p = .129 to .541) for glucose over time, AUC, or iAUC, there was a main effect for sex for glucose over time (p = .004) and AUC (p = .006), but not iAUC (p = .125). Females had higher blood glucose throughout each trial (22% (13 to 31%), p = .004) but both males' and females’ postprandial blood glucose was lowered following 10 min of SCD relative to the seated control condition. Conclusions: Males and females benefited equally from single, short SCD bouts of low to moderate intensity despite females having higher blood glucose at all time points. Previous findings of sex differences in the attenuating effect of exercise on postprandial blood glucose are likely due to the use of absolute workloads leading to varying relative intensities.